2009
DOI: 10.1007/s11743-009-1122-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microemulsion Systems Formed by a Mixed 1,3‐Dioxolane Ethoxylate/Octyl Glucoside Surfactant System

Abstract: The phase behavior of microemulsion systems containing water (or 1.0 wt% NaCl aq ), isooctane, and the binary surfactant system consisting of n-octyl-b-D-glucopyranoside, C 8 bG 1 , and the acid-cleavable alkyl ethoxylate, 4-CH 3 O (CH 2 CH 2 O) 7.2 , 2-(CH 2 ) 12 CH 3 , 2-(CH 2 )CH 3 ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…2C. The conditions employed produce W III systems, except at 50°C, which resulted in a W II system, in agreement with phase diagrams reported by our group [22]. The middle phase volume fraction for the system formed at 40°C was quite small.…”
Section: Partitioning Of Ck-213-e N In Binary Surfactant Microemulsisupporting
confidence: 89%
See 1 more Smart Citation
“…2C. The conditions employed produce W III systems, except at 50°C, which resulted in a W II system, in agreement with phase diagrams reported by our group [22]. The middle phase volume fraction for the system formed at 40°C was quite small.…”
Section: Partitioning Of Ck-213-e N In Binary Surfactant Microemulsisupporting
confidence: 89%
“…One such binary system is CK-2,13-E 5.6,ave /alkyl b-glucoside (C8bG1), which readily forms temperature-insensitive microemulsions phases with potential applicability to drug delivery [22]. Temperatureinsensitive microemulsions were also reported for the water/ C10bG1/C 6 E 2 /n-octane system when an equal mass of each surfactant was employed [23,24].…”
Section: Partitioning Of Ck-213-e N In Binary Surfactant Microemulsimentioning
confidence: 99%
“…It has been shown that a biobased surfactant synthesized by the enzyme-catalysed method can enhance oil recovery by interfacial activity and reverse wetting of reservoir rocks [29]. The viability of this method will be improved by further development of more stable and active biocatalysts and new technology in the bioprocessing field [30].…”
Section: Introductionmentioning
confidence: 99%